Snacking patterns among Chilean children and adolescents: is there potential for improvement? - Jensen, Melissa L (Public Health Nutr, 2019)
OBJECTIVE: To examine snacking patterns, food sources and nutrient profiles of snacks in low- and middle-income Chilean children and adolescents. DESIGN: Cross-sectional. Dietary data were collected via 24 h food recalls. We determined the proportion of snackers, snacks per day and energy from top food and beverage groups consumed. We compared the nutrient profile (energy, sodium, total sugars and saturated fat) of snacks v. meals. SETTING: South-east region of Chile. PARTICIPANTS: Children and adolescents from two cohorts: the Food Environment Chilean Cohort (n 958, 4–6 years old) and the Growth and Obesity Cohort Study (n 752, 12–14 years old). RESULTS: With a mean of 2·30 (se 0·03) snacks consumed daily, 95·2 % of children and 89·9 % of adolescents reported at least one snacking event. Snacks contributed on average 1506 kJ/d (360 kcal/d) in snacking children and 2218 kJ/d (530 kcal/d) in snacking adolescents (29·0 and 27·4 % daily energy contribution, respectively). Grain-based desserts, salty snacks, other sweets and desserts, dairy foods and cereal-based foods contributed the most energy from snacks in the overall sample. For meals, cereal-based foods, dairy beverages, meat and meat substitutes, oils and fats, and fruits and vegetables were the top energy contributors. CONCLUSIONS: Widespread snacking among Chilean youth provides over a quarter of their daily energy and includes foods generally considered high in energy, saturated fat, sodium and/or total sugars. Future research should explore whether snacking behaviours change as the result of Chile’s national regulations on food marketing, labelling and school environments.